Fitter Women Did Not Have Attenuated Hemodynamic Responses to Psychological Stress Compared with Age-Matched Women with Lower Levels of Fitness. - Sisitha U Jayasinghe; Susan J Torres; Mais Hussein; Steve F Fraser; Gavin W Lambert; Anne I Turner (PLoS ONE, 2017)
According to the 'cross stressor adaptation hypothesis', regular exercise acts as a buffer against the detrimental effects of stress. Nevertheless, evidence that higher levels of cardiorespiratory fitness moderate hemodynamic responses to acute psychological stress is inconclusive, especially in women. Women aged 30-50 years (in the mid-follicular phase of the menstrual cycle) with higher (n = 17) and lower (n = 17) levels of fitness were subjected to a Trier Social Stress Test (TSST). Continuous, non-invasive measurements were made of beat-to-beat, systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), heart rate (HR), stroke volume (SV), cardiac output (CO), left ventricular ejection time (LVET), maximum slope, pulse interval (PI) and total peripheral resistance (TPR). Maximal oxygen consumption was significantly (p<0.001) higher in the 'higher fit' women. Lower fit women had higher fasting glucose, resting heart rate, waist to hip ratios and elevated serum triglyceride and cholesterol/ HDL ratios compared with higher fit women (p<0.05 for all). While all measured parameters (for both groups)displayed significant (p<0.001) responses to the TSST, only HR, PI and LVET differed significantly between higher and lower fit women (p<0.001 for all) with the higher fit women having the larger response in each case. It was also found that higher fit women had significantly shorter time to recovery for maximum slope compared with the lower fit women. These findings provide little support for the notion that higher levels of cardiorespiratory fitness result in lower cardiovascular responsivity to psychological stress in women but may indicate that lower fit women have blunted responses to stress.